Determinant Improving the Quality of Financial Reports Pematangsiantar City Government - Silitonga, Hery Pandapotan; Sianipar, Ruth Tridianty; Putri, Juan Anastasia; Siregar, Robert Tua; Sudirman, Acai (E-Jurnal Akuntansi, 2022)
This study aims to determine the effectiveness of SPIP and organizational culture impact the successful implementation of SIKD in improving the quality of financial reports. A quantitative approach was used in this study with a literature and field design. The data sources used are primary data and secondary data. The data analysis technique used in this study was path analysis. The results showed that the t-test of the sub-structure model 1 of SPIP affected the success of SIKD implementation, organizational culture affected the success of the implementation of SIKD, and the t-test of the sub-structure model 2 showed that SPIP affected the quality of financial reports. organizational culture does not affect the quality of financial statements, and SIKD affects financial reports' quality. Furthermore, the effectiveness of the application of SIKD is an intermediary variable that affects the quality of financial reports in the Pematangsiantar City government. Keywords : SPIP; Organizational Culture; SIKD; Financial Report Quality.